Development Of Intersecting And Non-Intersecting Volumetric Feature Recognition Techniques In A Platform-Dependent System - Hayasi, Mohammad (2008)

(untitled)
The feature recognition process has been considered as the input for Computer-aided Process Planning through two different standpoints in implementation, one is nonfeature-based and the other is feature-based .The first one is done via accessing to the information of part (e.g. edges, faces,…) from within standard files with neutral data format (DXF/IGES/STEP) and then is conducted by connecting to the objects library of design-by-feature solid modeler. The second method has currently received extensive attention due to accessing to significant information effortlessly and handling intersecting and non-intersecting features. In this thesis, the feature-based design is exploited for converting design feature into manufacturing feature aimed to recognize the various intersecting and non-intersecting volumetric features. The rule-based, graph-based, and mathematical algorithms are used to recognize the intersecting and non-intersecting features with their volume. The ability and robustness of proposed methods in identifying the protrusion/subtractive features which are made on slanting/planar surfaces, is represented by implementing software on a commercial Computer-aided design package, Autodesk Inventor.